Współzależność rozwoju gospodarczego i demograficznego makroregionów ekonomicznych (na przykładzie RFN i Berlina Zachodniego) - Roeske-Słomka, Iwona (Wydział Prawa i Administracji UAM, 1976)
The author has endevoured the following aims. 1. to find certain statistical and mathematical methods which may be used for the research of the impact of the economic development upon the demographic one; 2. to elaborate the measures of economic and demographic development of macro-regions; 3. to verify both: methods and measures using data for the macro-regions of the Federal Republic of Germany during recent 20 years.
The Research and Analysis of the Interdependence between the Economic and Demographic Development of Macro-Regions. Case Study o f the Federal Republic of Germany